2010
DOI: 10.4269/ajtmh.2010.10-0066
|View full text |Cite
|
Sign up to set email alerts
|

Sulfadoxine-Pyrimethamine–Based Intermittent Preventive Treatment, Bed Net Use, and Antenatal Care during Pregnancy: Demographic Trends and Impact on the Health of Newborns in the Kassena Nankana District, Northeastern Ghana

Abstract: Demographics and health practices of 2,232 pregnant women in rural northeastern Ghana and characteristics of their 2,279 newborns were analyzed to determine benefits associated with intermittent preventive treatment (IPTp), antenatal care, and/or bed net use during pregnancy. More than half reported bed net use, 90% reported at least two antenatal care visits, and > 82% took at least one IPTp dose of sulfadoxine-pyrimethamine. Most used a bed net and IPTp (45%) or IPTp alone (38%). Low birth weight (< 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The prevalence of low birth weight as found in the current study seems not to have changed since an earlier report from the same health facility by Oduro and colleagues eight years ago [23]. Intermittent preventive treatment of malaria in pregnancy using sulfadoxine-pyrimethamine (IPTp - SP) is however known to be effective in reducing maternal malaria episodes, low birth weight, and preterm delivery [21, 24, 25].…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence of low birth weight as found in the current study seems not to have changed since an earlier report from the same health facility by Oduro and colleagues eight years ago [23]. Intermittent preventive treatment of malaria in pregnancy using sulfadoxine-pyrimethamine (IPTp - SP) is however known to be effective in reducing maternal malaria episodes, low birth weight, and preterm delivery [21, 24, 25].…”
Section: Discussionmentioning
confidence: 57%
“…Similar finding has been reported by Brabin et al 30 Non use of ITNs was found to be significant independent risk factor for fetal anaemia in this study (P = 0.01) This is due to increased risk of placental parasitaemia associated with non-use of ITNs. 23 Placental malaria was significantly associated with low birth weight in this study. The malaria parasites either directly cause mechanical compromise of placental circulation via widespread trophoblast membrane thickening, increased fibrinoid necrosis and cytotrophoblast prominence or indirectly interfere with placental function and induce pathological lesions.…”
Section: Discussionmentioning
confidence: 62%
“…The WHO goal of four ANC visits was met by more than 70% of the interviewed women. This is considerable when compared to West and East Africa [9,15-17]. Improvement of strategies for pregnant woman care can explain this high attendance.…”
Section: Discussionmentioning
confidence: 99%